How do interprofessional practice teams work together to identify and provide for gifted students with multiple exceptionalities? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Palmerston North, New Zealand - O'Brien, Jilly (Massey University, 2014)
Whilst there is some international research regarding multidisciplinary collaboration as a means to identify and meet the needs of gifted learners with multiple exceptionalities, there is little New Zealand based information, much less research, on this practice. This multiple case study research explored how gifted learners with multiple exceptionalities are supported in New Zealand by interprofessional (IPP) teams of teachers, special needs coordinators, gifted and talented coordinators, educational psychologists, school counsellors, resource teachers and others. The purpose of the study was to explore experiences and understandings around how IPP teams work against core competencies of interprofessional practice. These are shared values, roles and responsibilities, communication, and teamwork. Key findings of this study were that the interprofessional practice team identity is still in its infancy, with core competencies not fully developed. Whilst there were shared values and a willingness towards recognising inclusive practices for gifted learners with multiple exceptionalities, these shared values were hampered by limited knowledge and expertise across the IPP team. Limited understandings of teamwork processes, and limited recognition of the importance of communication within the IPP team were common themes. Parents were seldom considered, and students were never considered part of the IPP team, which by its very name excludes parent and student voice. Whilst not evaluative, these findings show that gifted learners with multiple exceptionalities in New Zealand may not have adequate support at a systems level. Recommendations include the development of interprofessional practice competencies as one way to ensure gifted learners with multiple exceptionalities and their whanau experience full inclusion in our education system, and more research to evaluate whether effective IPP teams translate to more positive student outcomes.
Keywords: Gifted children; Gifted learners; Interprofessional teams; Interprofessional practice